The World Society of Emergency Surgery (WSES) spleen trauma classification: a useful tool in the management of splenic trauma - Federico Coccolini; Paola Fugazzola; Lucia Morganti; Marco Ceresoli; Stefano Magnone; Giulia Montori; Matteo Tomasoni; Stefano Maccatrozzo; Niccolò Allievi; Savino Occhionorelli; Yoram Kluger; Massimo Sartelli; et al. (World Journal of Emergency Surgery, 2019)
Abstract Background The World Society of Emergency Surgery (WSES) spleen trauma classification meets the need of an evolution of the current anatomical spleen injury scale considering both the anatomical lesions and their physiologic effect. The aim of the present study is to evaluate the efficacy and trustfulness of the WSES classification as a tool in the decision-making process during spleen trauma management. Methods Multicenter prospective observational study on adult patients with blunt splenic trauma managed between 2014 and 2016 in two Italian trauma centers (ASST Papa Giovanni XXIII in Bergamo and Sant’Anna University Hospital in Ferrara). Risk factors for operative management at the arrival of the patient and as a definitive treatment were analyzed. Moreover, the association between the different WSES grades of injury and the definitive management was analyzed. Results One hundred twenty-four patients were included. At multivariate analysis, a WSES splenic injury grade IV is a risk factor for the operative management both at the arrival of the patients and as a definitive treatment. WSES splenic injury grade III is a risk factor for angioembolization. Conclusions The WSES classification is a good and reliable tool in the decision-making process in splenic trauma management.